Investigation of the liquid-vapor equilibrium in the mixture of carbon dioxide and normal alkanes in binary systems using the Peng-Robinson equation of state modified with mixing rules - Ahad Khaghani; Mojtaba Saei Moghaddam; Mohammad Fani Kheshti (Chemical Thermodynamics and Thermal Analysis)
This study uses the Peng-Robinson equation of state to investigate the vapor-liquid equilibrium in binary and non-ideal systems that contain CO2 and normal alkanes. The classic van der Waals mixing rule with binary interaction parameters enhanced by the Jaubert et al. aggregation model is employed, along with the Wong-Sandler mixing rule as a G-Excess model to improve phase equilibrium calculations. Results show that the Peng-Robinson model alone has average errors of 5.82 % in the vapor phase and 7.24 % in the liquid phase, emphasizing the need for binary interaction coefficients for accuracy. Incorporating these coefficients reduces errors to 0.85 % in the vapor phase and 1.33 % in the liquid phase. Furthermore, combining the Peng-Robinson model with Jaubert et al.'s model yields average errors of 1.26 % in the vapor phase and 1.95 % in the liquid phase while utilizing the Wong-Sandler mixing rule as a G-Excess model to improve phase equilibrium calc mixing rule with three fitted coefficients results in errors of 1.02 % and 1.30 %, respectively. For binary mixtures of CO2 and hydrocarbons lighter than C10, the Wong-Sandler mixing rule, binary interaction coefficient, and Jaubert et al. fitting model improve the VLE predictions in the vapor phase by 82.45 %, 85.40 %, and 78.33 %, respectively. In the liquid phase, these methods improve the predictions by 81.95 %, 81.62 %, and 73.02 %, respectively. These findings provide valuable insights for industries dealing with CO2 and normal alkane mixtures, offering opportunities for enhanced accuracy in various industrial applications.